Oportunidades Program Participation and Body Mass Index, Blood Pressure, and Self-Reported Health in Mexican Adults - MBA, Xiaohui Hou, PhD; Paul J. Gertler, PhD; Lia C. H. Fernald, PhD (Centers for Disease Control and Prevention, 2008)
IntroductionGovernments around the world are seeking to address the increasing prevalence of obesity and hypertension. Our objective was to evaluate the effect of an incentive-based development program (Oportunidades, formerly Progresa) on body mass index (BMI), blood pressure, and self-reported health.MethodsAn intervention group of low-income (below the 20th percentile nationally), rural, Mexican adults (aged 30-65 years) (n = 5280) received program benefits (cash transfers contingent on positive changes in health behavior such as regular health checkups) for 3.5 to 5.0 years. They were compared with a newly recruited control group of adults (n = 1063) who had not yet begun receiving benefits. Analyses were adjusted for almost 50 social and economic covariates.ResultsAge- and sex-adjusted BMI was lower in adults from intervention communities than in those from control communities (26.57 kg/m2 vs 27.16 kg/m2, P < .001), as was the prevalence of obesity (20.28% vs 25.31%, P < .001) and overweight (59.24% vs 63.04%, P = .03); these results were attenuated after covariates were included. Adults in intervention communities had a lower combined prevalence of uncontrolled hypertension (33.80% vs 34.52%, P = .008) when adjusting for all covariates. Mean systolic (β = -2.60, P < .001) and diastolic (β = -2.84, P < .001) blood pressures were significantly lower in the intervention communities after all covariates were included, and self-reported health outcomes were better.ConclusionsParticipation in Oportunidades, a large-scale cash-transfer program, was associated with lower prevalence of obesity and hypertension and better self-reported health in adults in rural Mexico.